2019
DOI: 10.21608/ajs.2018.35614
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR FOR ANTIOXIDANT GENES FROM EGYPTIAN GRAY MANGROVE Avicennia marina UNDER SALT STRESS TO NABQ PROTECTED AREA

Abstract: RT-PCR was conducted for four genes implicated for salt tolerance, oxidative and osmotic stresses in Egyptian gray mangroves within Nabq protected area in South Sinai Governorate. The results showed over-expression of the mRNA of ferritin (amFer1) gene as very high expression, followed by increase in mRNA of superoxide dismutase (amSOD1) and ubiquitin conjugation2 (amUBC2). At the same time gene expression of catalase (amCAT1) decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The amCat1 gene was downregulated relative to the amSod1 gene, which was up-regulated; meanwhile, the amUBC2 gene was moderately expressed. Moreover, the results showed that the amFerI gene was a more up-regulated than the other three genes (Elatawy et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The amCat1 gene was downregulated relative to the amSod1 gene, which was up-regulated; meanwhile, the amUBC2 gene was moderately expressed. Moreover, the results showed that the amFerI gene was a more up-regulated than the other three genes (Elatawy et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the structural 3'-UTR regions of all four genes (amCat, amFer, amSOD, and amUBC2) revealed that the amCat1 (99%), amFe1r (99%), amSOD1 (98%), and UBC2 (100%) genes were substantially similar. Furthermore, in Egyptian gray mangroves (A. marina) grown on South Sinai reserves under diverse environmental conditions, all four genes are important for controlling abiotic stresses, such as oxidative and osmotic stress (Abdel-Tawab et al, 2018). Meanwhile, the Ubc1 and Ubc2 genes are up-regulated in response to abiotic stresses, including salt stress, osmotic and ionic tolerances, and oxidative stress via modulating the MYB42-mediated expression of the SOS2 pathway (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%